OBSERVATIONS OF FLEXURE AND THE RHEOLOGY OF THE OCEANIC LITHOSPHERE - Bodine, J; Steckler, M; Watts, A (1981)
Observations of flexure indicate that the effective flexural rigidity of oceanic lithosphere is a function of the age of the lithosphere at the time of loading, and hence temperature. We have used a yield stress envelope model constrained by data from experimental rock mechanics to determine how the flexural parameters and rheologic properties of oceanic lithosphere are related. The results of our model for seamounts and oceanic island loads in the interior of plates suggest that following loading, rapid stress relaxation occurs as the plate 'thins' from its short-term to its long-term (more than 106yr) mechanical thickness. The mechanical thickness, which determines the effective flexural rigidity of the plate, is strongly dependent on temperature and weakly dependent on load size and duration (more than 1-10Ma). The results of our model for convergent plate boundaries suggest that change in the shape of the Outer Rise along an individual trench system may be due to variations in the horizonal load acting across the boundary (less than 1kbar). The model predicts a narrow zone of high strain accumulation seaward of a trench which is in agreement with variations in crustal velocities and seismicity patterns observed along some trench systems. -Authors